Effects of highway runoff on streamflow and water quality in the Sevenmile Creek basin, a rural area in the Piedmont Province of North Carolina, July 1981 to July 1982 - 272305 Harned, Douglas (Washington, D.C. : U.S. Govt. Print. Off. ; Denver, CO : For sale by the Books and Open-File Reports Section, U.S. Geological Survey, 1988)
Bibliography: p. 32-33.